Work engagement and motivation influence business innovation among Peruvian workers - Tingal-Tafur, Flor Marleny; Santisteban-Yesquen, Juan Gabriel; Geraldo-Campos, Luis Alberto (LACCEI, 2025)
Having committed and always motivated employees is a challenge for companies because, in an environment of constant change, constant innovation is required. This is a concern of every entrepreneur, shareholder or investor. For this reason, this study reviews the relationship between work engagement and motivation and business innovation; in addition, the mediating role of work motivation is determined. A multivariate study based on cross-sectional mediation was used, in which 188 workers were studied. The data were stored in Excel and their descriptive, correlational and mediation analysis was performed with the Jamovi 2.2.5 program. The results reported significant levels of correlation between entrepreneurial innovation and motivation (r = 0.54***) and work engagement (r = 0.40). In turn, the latter two variables were related to each other (r = 0.44). In addition, the mediation model showed that motivation plays a partial moderating role between work engagement and entrepreneurial innovation (β = 0.195; p < 0.001). The results may be useful for implementing strategies to improve work engagement and employee motivation, which in turn may generate business innovation. Therefore, companies should foster motivation and work engagement to generate a culture of innovation.